MANAJEMEN LEMBAGA PENDIDIKAN ISLAM MENGHADAPI TANTANGAN GLOBALISASI - Aisyah Tidjani (Reflektika, 2017)
The advancement of science and technology has a serious impact on human life. The negative effects of globalization and the environmental crisis must be faced by Muslims. Islamic education must be able to build a strong Muslim generation through quality and qualified Islamic education which capable of “mastering”-not “mastered by”- knowledge and technology. This paper seeks to analyze the causes of the low quality of Muslim resources and the advancement of science and technology. This study focuses on the management of Islamic educational institutions to face the challenges of globalization. Therefore, Islamic education needs to reformulate in order to find a solution to the problems that have been faced by society. As the result, it must go through many things: firstly, the reconstruction of a contextual-critical Islamic education paradigm. Secondly, the reorientation of the goals and curriculum of Islamic education. Thirdly, the reorientation of Islamic human resource management and development. And fourthly, the democratization of Islamic education and the creation of alternative Islamic educational institutions.